Assessment of Bataan, Mariveles Dam using modelling and GIS watershed sediment load, reservoir capacity and dam spillway operation - Conanan, Justine Anne S.; Herrera, Eugene C. (Quezon City College of Engineering, University of the Philippines Diliman, 2017)
The Freeport Area of Bataan is a special economic zone whose water supply is solely dependent on the Mariveles Dam. The Dam was built in the 1970's and is currently being operated without design specifications since there are no existing records of the dam design and operational manual. Over the past 40 years, the hydrology of the dam watershed has changed and placed the dam at risk of accumulating too much sediment at its reservoir. The study aims to verify this change using the Soil and Water Assessment Tool (SWAT) by simulating the long-term watershed hydrology, and consequently the sediment fluxes of its watershed from 1979 to 2014. Rainfall and evaporation data, topographic, land- and soil-cover information of the study site were used in the analysis, as well as bathymetric data of the Mariveles Dam reservoir. The average yearly dry and wet season precipitations were 637 mm and 2,702 mm, respectively, with a computed average sediment yield of 3.1ton/ha/year. With the use of ArcGIS, available reservoir bathymetric data was analyzed, resulting to a computed storage capacity of 5,480,272 mo, which is approximately 20% less than its design capacity. This can be a satisfactory account of the reservoir's sediment accumulation over years of operation. Sedimentation flux projections using the computed average sediment yield determined that in the next 20 and 40 years, the storage capacity will be 30% and 40% smaller than its design storage with capacities of 4,745,184.43 m3 and 4,045,101.03 m3, respectively. An updated rating curve was generated accordingly, utilizing the information from hydraulic analysis, for more precise spillway discharge operations.
Thesis (Bachelor of Science in Civil Engineering)--University of the Philippines Diliman
Keywords: Dams -- Philippines -- Bataan (Province); Dams -- Evaluation